Kata Serapan Sanskerta dalam Bahasa Bali dan Bahasa Thailand - Siriporn Maneechukate; Hertiki Hertiki (Aksara, 2025)
This research studies Sanskrit loanwords appearing in Balinese and Thai languages with the aim of analyzing the relationships in terms of phonetic systems, syllable structures, word types, and meanings of Sanskrit loanwords in both languages. The study focuses specifically on 378 Sanskrit loanwords in Balinese and Thai that share the same Sanskrit roots. The results show that certain consonant and vowel sounds in Sanskrit loanwords in Balinese correspond to two different consonant and vowel sounds in Sanskrit loanwords in Thai. This discrepancy may be due to the smaller number of consonant and vowel sounds in Balinese compared to Thai. Sanskrit loanwords in Balinese tend to have more open syllable structures than those in Thai, indicating that the syllable structures of Sanskrit loanwords in Balinese are closer to the original Sanskrit forms than those in Thai. The types of Sanskrit loanwords in both Balinese and Thai can be divided into two main categories: those with matching types and those with differing types. Regarding meanings, the study found that the meanings of Sanskrit loanwords in Balinese and Thai can be categorized into five groups: (1) loanwords with identical meanings, which is the most common group; (2) loanwords with similar meanings; (3) loanwords with different meanings; (4) loanwords with extended meanings; and (5) loanwords with reduced meanings. These findings indicate that even though both languages borrow the same Sanskrit words, the integration into each language follows its own system and usage. AbstrakPenelitian ini bertujuan untuk membandingkan kosakata Sansekerta dalam bahasa Thai dan Bali. Kajian ini mengkaji kosakata serapan dari bahasa Sanskerta yang terdapat dalam bahasa Bali dan Thai, dengan fokus pada analisis keselarasan sistem fonetik dan struktur suku kata, jenis kata, serta makna kosakata serapan tersebut. Penelitian ini secara khusus mengamati 378 kata serapan Sanskerta yang digunakan dalam kedua bahasa, yang berasal dari akar kata Sanskerta yang sama. Hasil menunjukkan adanya kesesuaian antara beberapa bunyi konsonan dan vokal pada kata serapan Sanskerta dalam bahasa Bali dengan padanannya dalam bahasa Thai, yaitu berupa dua bunyi konsonan dan vokal. Perbedaan ini muncul karena bahasa Bali memiliki jumlah bunyi konsonan dan vokal yang lebih terbatas dibandingkan bahasa Thai. Kata-kata dari Sanskerta yang diserap ke dalam bahasa Bali umumnya memiliki struktur suku kata terbuka yang lebih banyak dibandingkan dengan kosakata serupa yang masuk ke bahasa Thai, mengindikasikan bahwa bentuk kata serapan Sanskerta dalam bahasa Bali lebih dekat dengan bentuk aslinya daripada dalam bahasa Thai. Kata serapan Sanskerta dalam kedua bahasa, Bali dan Thai, dapat dikelompokkan menjadi dua jenis utama: yang mempertahankan jenis kata yang sama dan yang mengalami perubahan jenis kata. Berdasarkan analisis makna, ditemukan lima kategori utama: (1) kata serapan dengan makna yang identik (kelompok terbanyak); (2) kata serapan dengan makna yang serupa; (3) kata serapan dengan makna yang berbeda; (4) kata serapan dengan makna tambahan; dan (5) kata serapan Sansekerta dengan makna yang lebih sempit. Kesimpulan penelitian ini adalah, meski kedua bahasa mengadopsi kata dari sumber yang sama, yaitu Sanskerta, proses adaptasi dan penggunaannya berbeda pada masing-masing bahasa.